Low‐Pressure Plasma After‐Treatment of Pollutants Emitted During Semiconductor Manufacturing. Issue 6 (21st May 2015) - Hur, Min; Lee, Jae Ok; Kang, Woo Seok; Song, Young‐Hoon
<x xml:space="preserve">Abstract</x> Feasibility tests of abating and stabilizing pollutants emitted during semiconductor manufacturing are performed by using a plasma reactor placed before a vacuum pump. Abatement characteristics of N2O, CF4, CHF3, NF3, C3H6, and TEMAZ are investigated by analyzing the data obtained by using Fourier transform infrared spectroscopy and gas chromatography. The size of byproduct particles is identified by using a particle sampler. Analysis is focused on the role of reactant gases (O2 or H2O) during abatement. Finally, the applicability of low‐pressure plasma after‐treatment technology is discussed from the environmental and economic points of view.<inline-graphic xlink:href="ark:/27927/pgj11pxf982" content-type="ppap201500046-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />